Genomic Characterization Provides New Insights for Detailed Phage- Resistant Mechanism for Brucella abortus - Li, Xu-ming; Kang, Yao-xia; Lin, Liang; Jia, En-Hou; Piao, Dong-Ri; Jiang, Hai; Zhang, Cui-Cai; He, Jin; Chang, Yung-Fu; Guo, Xiao-Kui; Zhu, YongZhang (Frontiers in Microbiology, 2019)
As the causative agent of cattle brucellosis, Brucella abortus commonly exhibiting a smooth phenotype are typically lysed by Brucellaphages. This sensitivity are used as a basis for B. abortus taxonomy. We previously reported the discrepancy between traditional phenotypic typing and MLVA results of a smooth phage-resistant (SPR) strain Bab8416. Here, we further obtained a complete genome sequence of Bab8416 using a combination of multiple NGS technologies and PCR sequencing. The detailed genetic differences between B. abortus SPR Bab8416 and large smooth phage-sensitive (SPS) strains were investigated in comparative genomic study. The huge indels between SPS strains and Bab8416 showed two evolutionary branches that might have diverged at a far phylogenetic node. Compared to B. abortus SPS strain 9-941 (Bab9-941), the specific re-arrangement event in Bab8416 displaying a closer linear relationship with B. melitensis 16M than other B. aborus strains resulted in the truncation of c-di-GMP synthesis, and 3 c-di-GMP-metabolizing genes, were present in Bab8416 and B. melitensis 16M, but absent in Bab9-941 and other B.abortus strains, indicating a potential SPR mechanism. Moreover, despite almost completely intact smooth LPS related genes, only one mutated OmpA family protein of Bab8416, functionally related to flagellar and efflux pump, was identified. Several point mutations were identified to be Bab8416 specific while a majority of them were verified to be B. abortus ST2 characteristic. In conclusion, our study should play a significant role in refining and updating Brucella taxonomic schemes and provides new insights for further detailed analysis of mechanisms for Brucella phage resistance.